Influence of Personalized Product Recommendation, Online Review Stimuli, and Customer Brand Identification on Purchase Intention (Case Study on Bukalapak Consumers in Semarang) - Christina, Angelia -; Setiawan, Andi -; Prasetya, Budi - (JOBS (Jurnal Of Business Studies), 2023)
This study aims to analyze the influence of personalized product recommendation, online review stimuli, and customer brand identification on purchase intention of Bukalapak consumers in Semarang. Data collection method was non probability sampling with 100 people of Bukalapak consumers in Semarang. The analysis technique used in this research were vailidity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, linearity test, multiple linear regression, T test, F test and coefficient of determination. The data in this study were analyzed through SPSS 25. The analysis shows that personalized product recommendation (X1), online review stimuli (X2), and customer brand identification (X3) have a significant effect on purchase intention of Bukalapak consumers in Semarang. This research is expected to be a solution to determine the right marketing strategy in facing competition in the marketplace industry in Indonesia by applying personalized product recommendation, online review stimuli, and customer brand identification to increase purchase intention on Bukalapak